Method validation of Pb metal analysis in laboratory waste on phytoremediation of water hyacinth (Eichornia crassipes) with UV-Vis spectrophotometry - Malina, Lina; Kamelia, Yayan (Universitas Lambung Mangkurat, 2023)
Along with the rapid development of the times, the need for energy is also increasing. Fossil energy in Indonesia reaches 95% of Indonesia’s energy needs. For this reason, it is necessary to find a solution to overcome this, one of which is using renewable energy which must also be environmentally friendly. One alternative energy that has been discovered and is still being developed is biofuel. One of the raw materials that can be used for the production of biofuels is the microalgae Nannochloropsis sp. This study aimed to determine the effect of operating time on %yield and FFA of the biofuel produced and the effect of loading catalyst on %yield and FFA of the resulting biofuel. The highest %yield of crude and the lowest FFA were found at a reaction time of 3 hours and a catalyst loading of 0,45 %wt of 47,981 and 0,064 and the lowest %yield of crude and the highest FFA were at a reaction time of 1 hour with a catalyst loading of1 hour with a catalyst loading of 0,4 %wt of 25,730% and 0,133.